PHYTOCHEMICAL SCREENING, ANTIBACTERIAL AND INSECTICIDAL ACTIVITIES OF STEM BARK EXTRACTS OF BOSWELLIA DALZIELII HUTCHIN FROM KALTUNGO, NIGERIA - Mshelia, E. H.; Pindar, Watirahyel; Tadzabia, Kadam; Mohammed, A. H.; Ojo, Omolide (FUDMA Journal of Sciences, 2023)
The importance of traditional herbal medicinal system has now gained attention in developed and developing countries. Boswellia dalzielii is a tree grows in the wild usually in the Savannah region of West Africa. These work assessed the phytochemical constituents, antibacterial and insecticidal activities of the stem bark extracts of Boswellia dalzielii. The plant extracts were obtained using soxhlet method with petroleum ether, ethyl acetate, acetone, ethanol and water as solvents for 10 hours while the phytochemicals and insecticidal activities were determined using standard methods. The phytochemical screening showed significant presence of carbohydrate in the ethanol and water extracts while significant amount of tannin was detected only in the ethanol extract. The petroleum ether and ethyl acetate showed absence of carbohydrate, tannins, phlobotannin, cyanogenic glycoside, chlorogenic acid and alkaloid. Significant amount of flavonoid was seen in the water extract, while only the ethanolic extract showed significant amount of cardiac glycoside and alkaloid. The acetone extract showed significant quantity of alkaloid and terpenes and steroids. The antibacterial screening showed that ethanol extract had the highest inhibitory activity. The petroleum ether extract had the least active components with no activity on the test organisms. The insecticidal activity of the plant extracts showed that acetone extract had the highest insecticidal activity on both the test insects. Camponotus consobrinus shows the highest percentage mortality of 75% at a concentration of 500µg and LC50 of 1.64x102µg followed by the Acanthscelides obtectus with the percentage mortality of 53% at a concentration of 250µg and...
Keywords: Boswellia dalzielii; Phytochemical; Antibacterial; Insecticidal; Camponotus consobrinus; Acanthscelides obtectus